A calculation method of the passive wireless surface acoustic wave sensor response phase - Ha, Nguyen Thu; Thai, Trinh Van; Cung, Thanh Long; Hong, Hoang Si (Bulletin of Electrical Engineering and Informatics, 2023)
In this research, we propose a method to calculate the phase delay angle of the reflected wave compared to the wave emitted from the interdigital transducer (IDT) of a passive wireless surface acoustic wave (SAW) sensor by combining simulation of the finite element method (FEM) and MATLAB. Based on the result, we consider the influence of the reflector position on the phase delay of the SAW sensor consisting of an IDT and three equally spaced reflectors. The distances between the IDT and the first reflector are 870 micrometers, 939.6 micrometers, and 1009.2 micrometers, and the distances between the reflector positions are 452.4 micrometers, 522 micrometers, and 591.6 micrometers. The outputs of the FEM simulation, including delay time, amplitude loss, and the length of the reflected wave are put into the model in MATLAB to determine the phase delay of the response waves. The obtained phase delay results show that as the distance between the IDT and the reflectors increases, the phase delay angle increases to 4.49 degrees, 5.39 degrees, and 5.78 degrees, respectively.